Low back pain in the adolescent athlete - Kraft, D. E. (Pediatric Clinics of North America, 2002)
This article about low back pain in the adolescent athlete contents: • History • Physical examination • Radiologic diagnosis • Pars interarticularis problems • Pars stress fracture • Spondylolysis • Spondylosisthesis • Lumbar disc herniation • SI joint pain • Mechanical/muscular low back pain • Summary • References